Network pharmacology-based analysis on bioactive anti-diabetic compounds in Potentilla discolor bunge. (15th September 2019) - Wang, Niannian; Zhu, Feifei; Shen, Mingxiang; Qiu, Lipeng; Tang, Min; Xia, Hengchuan; Chen, Liang; Yuan, Yi; Ma, Shangshang; Chen, Keping
Abstract: Ethnopharmacological relevance: Potentilla discolor Bunge (PDB) is a commonly used herbal for alleviating diabetes mellitus and its complications. Although accumulating evidences show the anti-diabetic efficacy of PDB, the vital anti-diabetic compounds and their functional targets remain elusive. Aim of the study: To investigate the anti-diabetic ingredients and their functional mechanisms in PDB, gas chromatograph -mass spectrometry analysis was performed on PDB extract and 21 were testified as anti-diabetic compounds. Materials and methods: Subsequently their potential protein targets were also identified. The bioinformatics analysis was implemented by network pharmacology-based approaches. STRING analysis was performed to reveal enrichment of these target proteins, protein-protein interactions, pathways and related diseases. Cytoscape was used to determine the potential protein targets for these components in PDB, indicating that 21 anti-diabetic compounds in PDB regulate 33 diabetes-related proteins in 28 signal pathways and involve 21 kinds of diabetes-related diseases. Among the 21 potential anti-diabetic components predicted by network analysis, tricetin was firstly experimentally validated at the molecular and cellular level. Results: Results indicated that this active small-molecule compound may have beneficial effects on improving glucose uptake. Conclusions: We envisage that network analysis will be useful in screening bioactive compounds of medicinal plants. Graphical abstract: Image 1